Florida Crop/Pest Management Profiles: Strawberry - Mark A. Mossler (EDIS)
Revised! CIR1239, a 9-page illustrated fact sheet by Mark A. Mossler, describes the Florida strawberry industry and outlines the potential pests of strawberry and their various methods of control. Includes references. Published by the UF Department of Agronomy, July 2010.